Tunable ultranarrow spectrum selective absorption in a graphene monolayer at terahertz frequency. (3rd May 2016) - Wu, Jun
Abstract: Complete absorption in a graphene monolayer at terahertz frequency through the critical coupling effect is investigated. It is achieved by sandwiching the graphene monolayer between a dielectric grating and a Bragg grating. The designed graphene absorber exhibits near-unity absorption at resonance but with an ultranarrow spectrum and antenna-like response, which is attributed to the combined effects of guided mode resonance with dielectric grating and the photonic band gap with Bragg grating. In addition to numerical simulation, the electric field distributions are also illustrated to provide a physical understanding of the perfect absorption effect. Furthermore, the absorption performance can be tuned by only changing the Fermi level of graphene, which is beneficial for real application. It is believed that this study may be useful for designing next-generation graphene-based optoelectronic devices.